Can Experimental Electron‐Density Studies be Used as a Tool to Predict Biologically Relevant Properties of Low‐Molecular Weight Enzyme Ligands?. Issue 11 (20th August 2013) - Grabowsky, Simon; Jayatilaka, Dylan; Fink, Reinhold F.; Schirmeister, Tanja; Engels, Bernd
Abstract The case of protease inhibitor model compounds incorporating an aziridine or epoxide ring is used to exemplify how application of experimental electron‐density techniques can be used to explain the biological properties of low‐molecular weight enzyme ligands. This is furthermore seen in the light of a comparison of crystal and enzyme environments employing QM/MM computations to elucidate to which extent the properties in the crystal can be used to predict behavior in the biological surrounding.